Physical giftedness/talent: A systematic review of the literature on identification and development - Jung, Jae Yup (Frontiers in Psychology, 2022)
In this study, a systematic review was undertaken of the international scholarly literature on the identification and development of giftedness/talent in the physical domain, to establish the scope of current knowledge in the area. To identify relevant research, a search that involved the creation of a search string and the manual examination of the titles and abstracts of potentially relevant research, was conducted using two databases – Web of Science Core Collection and SportDiscus – and six inclusion/exclusion criteria (i.e., relevance to identification or development of physical giftedness/talent, an empirical study, publication in a reputable academic peer-reviewed journal, publication from 2000 to 2021, an English language publication, and authorship by scholars based in any part of the world). The 101 journal articles that met the inclusion/exclusion criteria were analysed for key details, including the year of publication, methodological approaches, participants, and major findings. The five broad themes that emerged from the findings of these articles related to conceptions of physical giftedness/talent, identification characteristics/criteria, factors associated with identification, identification methods, and talent development interventions. An outline and discussion of the key issues and trends in the research, along with some recommendations for future research, conclude the systematic review.